A COMUNICAÇÃO COMUNITÁRIA DOS QUILOMBOLAS CARRAPATOS DA TABATINGA: O DIÁLOGO COMO PRÁXIS DA COMUNICAÇÃO INTERPESSOAL E GRUPAL - Sgoti, Silmara de Mattos (2016)
The study emphasizes community communication of Quilombolas Carrapatos of Tabatinga, community located in Bom Despacho in the State of Minas Gerais. The objectives are to understand systematically and scientifically based communication processes of participatory and management practices within the community, as well as check for a work in the group or media community outreach or local media to amplify the demands social rights of quilombos in Bom Despacho. The literature built the theoretical framework on communities, community communication and a brief explanation of the Quilombo as a symbol of resistance in Brazil. We used ethnographic research, in the dialectic of parameters, with the support of participant observation in the field of research in certain activities and not permanently, which allowed an on-site study. Additional technical data collection were applied: the interview semi-structured in order to get a clear community descriptions to and interconnecting links in the cultural milieu that is inserted: their black ancestry, the real and symbolic territory and the interaction with the local society. The interviews were with community leaders, community members and some actors of local society. The study of document analysis was complemented regarding quoted Quilombo and secondary data as information already available in public and private bodies or institutions linked to the community. At the conclusion of the study it was found that dialogue is the practice of interpersonal communication and community group of Quilombolas Carrapatos of Tabatinga. In the communication processes between the members of the critical dialogue community is present in discussions about the social demands as the importance quilombo identity, valuing the memory of slave ancestors, the need to resist the prejudice and social inequality in the local society, and the struggle for the constitutional right to repossess the quilombo territories. The community has a dialogical communication with the local society through cultural events, such as the Congado in which it was found the connecting force of social demands in songs, dances and costumes. There is community participation in Bom Despacho media in assigned spaces, sporadically, on commercial radio for dissemination of the cultural events and activities. The community uses social network to publish their content to be a medium of low cost and high coverage. It was found in the city of Bom Despacho no work in group or media community outreach or local, to amplify the social demands of the Quilombo las Carrapatos of Tabatinga. The exercise of community citizenship in Bom Despacho is impaired due to low representation in municipal government by a minority in the city, resulting in a lack of public policies to meet the social demands of the community. All community conquered came through the Federal Government.